The international law on ballast water : preventing biopollution - Rolim, Maria Helena Fonseca de Souza (Publications on ocean development ;, 2008)
Providing an overview of the legal aspects related to marine pollution caused by ballast water and tank sediments, this book offers an analysis of the international legal system. It includes principles of international customary law and also references to an environmental treaty law, which relates the Ballast Water Convention to other treaties.